Mechanical Thrombectomy in Medium Vessels Occlusion (MeVOs): An Institutional Experience with M2 Divisions of Middle Cerebral Artery - Bheru Dan Charan; Gaikwad, Shailesh B; Jain, Savyasachi; Garg, Ajay; Devarajan Sebastian, Leve Joseph; Srivastava, M V Padma; Bhatia, Rohit; Pandit, Awadh Kishore; Kale, Shashank Sarad (Acta medica Lituanica, 2024)
Background: Mechanical thrombectomy has been established as a safe, standard and effective treatment option for occlusions of the proximal segment of the middle cerebral artery (MCA), as demonstrated in numerous studies. However, performing thrombectomy in the M2 divisions of MCA presents inherent challenges. In this institutional experience, we aim to delineate the recanalisation rates achieved through mechanical thrombectomy in cases involving the M2 segment of the MCA.Methods: We conducted a retrospective analysis of patients who underwent thrombectomy due to M2 MCA occlusions in the period from January 2018 to December 2021. Various factors affecting recanalisation rates were assessed.Results: A total of 15 patients with M2 segment occlusions of the middle cerebral artery were included in the study, comprising 11 in the superior division and 4 in the inferior division. The successful recanalisation rate was 72.33%, with notably higher success observed in cases of inferior division occlusion. The primary outcome of our study was the mTICI recanalisation status, categorised as successful recanalisation (mTICI = 2b or mTICI = 3) and unsuccessful recanalisation (mTICI = 1 or mTICI = 2a) and mRS at 6 months. None of the predictors assessed reached statistical significance.Conclusions: Mechanical thrombectomy demonstrates favourable efficacy and recanalisation rates in cases of M2 MCA division occlusion. Notably, inferior division occlusions exhibit a higher likelihood of successful recanalisation.